THE INFLUENCE OF PROMOTION AND BRAND IMAGE ON PURCHASING DECISIONS FOR POND'S PRODUCTS IN BOJONEGORO DISTRICT - Setiyawan, Ferdy; Aminah, Siti (International Journal of Multidisciplinary Research and Literature, 2024)
In the current era, people more often buy things that are not very important for their daily needs. Men and women who want to look attractive definitely need care products. Therefore, many cosmetic companies are competing to introduce their products to the public. On this basis, this research aims to determine and analyze the influence of promotion and brand image on purchasing decisions for Pond's products in Bojonegoro Regency. The population in this study were all buyers and users of Pond's in Bojonegoro Regency and sampling in this study used a non-probability sampling method with a total of 100 respondents. The measurement scale uses a Likert scale. The data used in this research is primary data, by distributing questionnaires to all Pond's buyers and users in Bojonegoro Regency. The analysis technique used is PLS (Partial Least Square) to see the causal relationship between variables. The test results show that promotions contribute to purchasing decisions and brand image contributes to purchasing decisions for Pond's products